1998
DOI: 10.1037/0022-3514.74.6.1670
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of coping assessed by ecological momentary assessment and retrospective recall.

Abstract: Recent research suggests that retrospective coping assessments may not correspond well with day-to-day reports. The authors extended this work by examining the correspondence between short-term (within 48 hr) retrospective coping reports and momentary reports recorded via a palm-top computer close in time to when the stressor occurred. There was relatively poor correspondence between the 2 assessments. Some reports of momentary coping were not reported retrospectively, and some coping reported retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
334
1
10

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(354 citation statements)
references
References 35 publications
(51 reference statements)
9
334
1
10
Order By: Relevance
“…To date, the few studies that have examined smoking and smoking cessation in homeless smokers have used focus groups or traditional lab/clinic based assessment methodology which may result in biased and/or inaccurate estimates due to recall biases and errors in memory (Shiffman et al, 1997;Stone et al, 1998). Such biases and errors may be particularly relevant in the moments/days leading up to a quit attempt, when potentially important momentary changes in key variables may be missed or misrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the few studies that have examined smoking and smoking cessation in homeless smokers have used focus groups or traditional lab/clinic based assessment methodology which may result in biased and/or inaccurate estimates due to recall biases and errors in memory (Shiffman et al, 1997;Stone et al, 1998). Such biases and errors may be particularly relevant in the moments/days leading up to a quit attempt, when potentially important momentary changes in key variables may be missed or misrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…This present research used the Experience Sampling Method Stone et al, 1998;Stone, Shiffman, & DeVries, 1999) to examine the somatic distress symptoms for a convenience sample of 50 Japanese and 61 Korean female college students. The women reported their distress experiences as ratings along a six-point rating scale once each day for seven days.…”
Section: Methods Design and Samplementioning
confidence: 99%
“…This present study examines the relationship among cultural group, depression symptoms and somatic symptoms for women in two countries within the broad "Asian" racial category. Specifically, we explore the nature of the similarities and differences among the somatic symptoms that co-occur with high BDI using the Experience Sampling Method Stone et al, 1998;Stone, Shiffman, & DeVries, 1999) to compare the somatic distress symptoms experienced by university women living in two Asian countries, Japan and Korea.…”
mentioning
confidence: 99%
“…The EMA methodology that will be used in this study is similar to that developed by Shiffman and colleagues [51,67,68] and was used in previous studies conducted by the investigative team. [69][70][71][72][73] EMA items will assess numerous constructs that are hypothesized to be related to the study outcomes (see Table 3).…”
Section: Programming the Mhealth Shared Resource At The Ouhsc And Stmentioning
confidence: 99%
“…[9,16,37,[46][47][48][49] Studies have indicated that traditional assessment methodologies provide biased and/or inaccurate estimates due to recall bias and errors in memory (e.g., assessing the number of drinks consumed or level of depression or anxiety over the past week or month). [50,51] Ecological momentary assessment (EMA), in which handheld devices are used to capture "real time" experiences that vary daily (or from moment to moment), is currently the most accurate way to measure phenomena in real time in natural settings. [50,52] Although EMA has been used in a variety of populations and with multiple health outcomes, only one study [53] outside of our own work [54] has collected EMA data in homeless adults.…”
Section: Introductionmentioning
confidence: 99%